Deficiency of Invariant Natural Killer T Cells Does Not Protect Against Obesity but Exacerbates Atherosclerosis in Ldlr−/− Mice - Savitha Subramanian (International Journal of Molecular Sciences, 2018)
Obesity is a chronic inflammatory state characterized by altered levels of adipose tissue immune cell populations. Natural killer T (NKT) cells are CD1d restricted lymphocyte subsets that recognize lipid antigens whose level decreases in obese adipose tissue. However, studies in mice with deficiency or increased levels of NKT cells have yielded contradictory results, so the exact role of these cells in obesity and adipose tissue inflammation is not yet established. We previously showed that Ldlr−/− mice with excess invariant NKT (iNKT) cells demonstrate significant weight gain, adiposity, metabolic abnormalities, and atherosclerosis. The current study evaluates the effects of NKT cell deficiency on obesity, associated metabolic changes, and atherosclerosis in Jα18−/−Ldlr−/− (lacking iNKT cells) and Cd1d−/−Ldlr−/− (lacking invariant and type II NKT cells) mice, and control mice were fed an obesogenic diet (high fat, sucrose, cholesterol) for 16 weeks. Contrary to expectations, Ja18−/−Ldlr−/− mice gained significantly more weight than Ldlr−/− or Cd1d−/−Ldlr−/− mice, developed hypertriglyceridemia, and had worsened adipose tissue inflammation. All the mice developed insulin resistance and hepatic triglyceride accumulation. Ja18−/−Ldlr−/− mice also had increased atherosclerotic lesion area. Our findings suggest that iNKT cells exacerbates the metabolic, inflammatory, and atherosclerotic features of diet-induced obesity. Further work is required to unravel the paradox of an apparently similar effect of iNKT cell surplus and depletion on obesity.